THE ROLE OF THE OCCUPATIONAL HEALTH NURSE IN PROMOTING THE HEALTH OF DELIVERY WORKERS: A LITERATURE REVIEW - Menon, Giulia Meneses; Sesnik, Heitor Hortensi; de Souza, Letícia Baio; Sala, Caroline; Xavier, Isabela Balini; Caniato, Maria Heloiza Bezerra; Gandolfo, Ana Glória Marroni; de Almeida, Maria Julia Elias; Rossa, Thais Amanda; Pereira, Natan David; Moura, Débora Regina de Oliveira (Seven Editora, 2025)
Introduction: Workers who rely on deliveries and travel for their livelihood are exposed to long working hours, family separation, adverse weather conditions, and unstable employment relationships, making them more susceptible to physical and mental illnesses. In this context, the role of the occupational health nurse becomes essential in health promotion and the prevention of occupational hazards. This study aims to analyze the contributions of occupational nursing to health promotion and disease prevention among drivers and delivery workers. Methodology: This is a descriptive study conducted through a literature review. The search was carried out in the Virtual Health Library (BVS) and the Scientific Electronic Library Online (SciELO), using descriptors combined with the Boolean operator AND: “Occupational Health,” “Drivers,” “Work,” “Digital Platforms,” and “Nursing.” After applying inclusion and exclusion criteria, eight studies were analyzed. Results and Discussion: The analyzed studies identified multiple risk factors among these workers, such as inadequate postures, noise exposure, sun exposure, stress, irregular eating habits, sleep deprivation, and the use of stimulant substances. The occupational health nurse plays a role in implementing programs and promoting health education focused on healthy habits and workplace safety. In addition, there was a growing use of digital technologies for remote health guidance for these workers, facilitating preventive interventions. Conclusion: It is concluded that the occupational health nurse plays a strategic role in the occupational health of drivers and delivery workers, contributing to the prevention of health problems, improvement of working conditions, and valuing of life, thus consolidating nursing as an essential element in health promotion within contemporary work contexts. DOI: https://doi.org/10.56238/sevened2025.037-051